Evaluating active travel and health economic impacts of small streetscape schemes: An exploratory study in London. (March 2019) - Aldred, Rachel; Croft, Joseph
Abstract: Introduction: This article proposes a low-cost approach that transport authorities can use to evaluate small-scale active travel interventions, including estimating health economic benefits from uptake of walking and/or cycling. Methods: Themethod combines post-intervention intercept surveys with the re-use of routinely collected count data. While inferior to more robust, longitudinal methods, the approach represents good value use of primary and secondary data at a far lower cost, for interventions unlikely otherwise to be evaluated at all. It makes use of government-supported tools that estimate physical activity health benefits from increased active travel. Findings: The article describes an example in which a residential street was closed to through motor traffic, which led to a decline of 90% in motor traffic volume and uplift in pedestrian and cycle counts. This example is exploratory in nature due to sample size (124 respondents). The intercept survey of pedestrians and cyclists found uplift in perceived quality of the local environment across various indicators. Results suggested that around a third of the increase in pedestrian and cycle counts post-scheme represents new journeys, mainly via mode shift, with most of the remaining two-thirds being diverted journeys. This information is used alongside the before-and-after count data to estimate new cycling and walking trips induced by the route improvement. Finally, the article estimates the health economic benefit resulting from increased physical activity, of approximately £500, 000 over 20 years. Conclusions: The article demonstrates a method for estimating active traveluptake and associated health benefits for smaller schemes. If applied over a number of schemes, the results could then be used to create an evidence base that could be used in assessing possible benefits of future schemes. Highlights: Evidence is lacking on how small streetscape changes affect active travel, hence health Paper demonstrates new approach to monitoring and evaluating small schemes Method combines count data, intercept surveys and health impact modelling Small-scale exploratory study (124 respondents) used to illustrate use of method Case study found health economic benefits of approximately £500, 000 over 20 years